Knowledge, Attitudes, and Practices Regarding COVID-19 Among Healthcare Workers in Venezuela: An Online Cross-Sectional Survey - Mendoza Millán, Daniela Lucía; Carrión-Nessi, Fhabián Stevens; Mejía Bernard, Mario Daniel; Marcano-Rojas, María Victoria; Omaña Ávila, Óscar Daniel; Doval Fernández, Juan Manuel; Chacón Labrador, Fabián Rafael; Quintero Rodríguez, Adriana; Gasparini Vega, Sebastian; Tami, Adriana; Maricuto, Andrea L.; Velásquez, Viledy L.; et al. (Frontiers in Public Health, 2021)
Background: The deterioration of Venezuela’s health system in recent years undoubtedly contributes to an increased impact of the COVID-19 pandemic. Understanding healthcare workers’ (HCWs) knowledge, attitudes, and practices (KAPs) towards COVID-19 in the early stages of the epidemic could inform their medical training to improve HCWs preparedness. Methods: A national cross-sectional online survey was conducted between May 26th and May 30th, 2020, to assess KAPs amongst HCWs in Venezuela. Results: A total of 1441 HCWs from all 24 regions of the country responded the survey. The mean age of the participants was 44 (SD 14) years; most were women (66.4%). Most participants were specialized physicians (48%), followed by nursing staff (13%) and resident doctors (12.3%). The majority of participants had good knowledge (76.3%), obtained information mainly from scientific literature (85.4%); had negative attitudes (53.6%), felt uncomfortable with their work during the current pandemic (59.8%); and reported appropriate practices (76.9%), yet participating in COVID-19 related training was absent in more than half of the HCWs. Positive attitudes were significantly more frequent in frontline workers than in non-frontline workers (p= 0.001). Bioanalysts, students and doctors were more likely to have good knowledge; participating in training was predictor for positive attitudes; older age was an appropriate practice predictor. Conclusions: HCWs knowledge in Venezuela could improve through the strengthening of education and training programs. The strategies should focus on reducing fear and improving attitudes towards the care of COVID-19 patients, as well as the promotion of preventive practices.